Analisis Pengaruh Kemiskinan Dan Ketimpangan Distribusi Pendapatan Terhadap Ketimpangan Gender Dalam Pendidikan Di Indonesia - Murbanto Sinaga; Rika Surianto Zalukhu; Daniel Collyn; Rapat Piter Sony Hutauruk; Suci Etri Jayanti S; Ayu Zurlaini Damanik; Sri Winda Hardiyanti Damanik (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
Gender inequality in education persists in Indonesia, as reflected in the differences in the Literacy Rate (AMH) between males and females. Therefore, this study aims to determine the influence of poverty and income distribution inequality on gender inequality in education in Indonesia, both partially and simultaneously. The study was conducted in 34 provinces in Indonesia. The data used were secondary data, including the poverty rate, the Gini ratio, and the Average Years of Schooling (RLS) in 2022. This research data was accessed online from the website of the Central Statistics Agency (BPS) at https://www.bps.go.id/id. Data analysis was performed using multiple linear regression analysis. The results indicate that income distribution inequality has a positive and significant impact on gender inequality in education in Indonesia. Meanwhile, poverty has a positive but not significant impact on gender inequality in education in Indonesia. Education and income distribution inequality simultaneously have a significant impact on gender inequality in education in Indonesia. The findings of this study have implications for policy formulation to achieve fair and equal human development.